Gresham’s Law, Inflation, Subjective Value Theory, Price Controls, and Usury in Don Quijote de la Mancha (Cultura Económica, 2018)
The author argues that Cervantes’s Don Quijote can be read in economic terms, and that it containslessons about the importance of political and monetary freedom. Through a detailed analysis of different episodes, the article presents the ways in which concepts such as Gresham’s Law, inflation, subjective value theory, price controls, and usury are depicted in the novel. Cervantes’s work shares much of the economic philosophy of the School of Salamanca, and this essay ultimately demonstrates that Don Quijote prompts readers to reflect on theproblems caused by economic practices that are directed against individual freedom.
Keywords: Don Quixote; Gresham’s Law; Subjective Value Theory; Price Controls; Inflation; Usury